Engaged or Not Engaged, That Is the Question: The Impact of Duality on the Participatory Experience of Augmented- Reality Interventions in Cultural Spaces - Jefferies, Liam (Mimesis Journal, 2024)
The fundamental power of augmented reality is its ability to utilize both physical and digital contexts to co-create meaning at their confluence and to deliver experiences that are greater than the sum of their parts. The article seeks to examine the theoretical and practical implications of the relationship between the physical and digital and to offer insight into how their interaction can impact, both positively and negatively, upon the participatory experience of visitors to cultural spaces. The article develops a framework to conceptualize and examine this relationship referred to here as duality. Duality, as a measure, is then applied to a number of case studies, two of which were created by the author, one being an interactive artwork, the other a site-specific educational application at a U.K. heritage site.